Cluster Biji Sawit Unggul Dengan Algoritma K-Medoids - Chandra Frenki Sianturi; Lince Tomoria Sianturi (BEES: Bulletin of Electrical and Electronics Engineering, 2022)
Superior oil palm seed is a plant derived from fruit that is 1.57 cm long and 0.92 cm wide, with a roundness of 80% and a weight of 1.11 grams. There have been a large number of 1.4 million oil palm seeds distributed by the end of 2021. There are several problem factors that influence choosing superior seeds for oil palm, namely the problem of circulating wild seeds and being traded on the illegal market, frequent pests and diseases in oil palm growth, coconut production capacity sufficient oil palm is still relatively lacking compared to demand, and many of the plantations are forcing the yield of oil palm fruit. the consequences of the problems above are the lack of knowledge and knowledge that can be obtained by anyone who has an oil palm plantation. So from the results of this study alternatives A1, A6, A9, A10, A13, A18 are in one cluster, and alternatives A2, A5, A8, A11, A14, A15, A16, A17, A19 are in one cluster, while alternative A3 ,A4,A7,A12,A20 are also in one cluster.